2022
DOI: 10.1111/cas.15649
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin reverses pyruvate kinase isoform M2‐mediated propranolol resistance in infantile hemangioma through reactive oxygen species‐induced autophagic dysfunction

Abstract: Infantile hemangioma is the most common benign vascular tumor of infancy, occurring in 5%-10% of mature newborns. 1,2 Infantile hemangioma is frequently characterized by a distinctive growth pattern with a rapid proliferative phase followed by spontaneous involution. 3 Currently, the primary clinical treatment methods for IH involve surgery, laser therapy, and drug therapy. 4 In 2008, Léauté-Labrèze et al. accidentally revealed that PRN, a nonselective βadrenergic receptor blocker, could efficiently slow down … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Furthermore, key glycolytic enzymes, including hexokinase 2,6-phosphofructo-2-kinase 3, pyruvate kinase M2 (PKM2) and lactate dehydrogenase A, are more highly expressed in HemECs than in HUVECs ( 25 ). PKM2 was demonstrated to play a critical role in regulating the progression of IH and the therapeutic resistance of propranolol treatment ( 26 ). Together, the results from these studies indicated that HemEC glucose metabolism participates in the development of IH ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, key glycolytic enzymes, including hexokinase 2,6-phosphofructo-2-kinase 3, pyruvate kinase M2 (PKM2) and lactate dehydrogenase A, are more highly expressed in HemECs than in HUVECs ( 25 ). PKM2 was demonstrated to play a critical role in regulating the progression of IH and the therapeutic resistance of propranolol treatment ( 26 ). Together, the results from these studies indicated that HemEC glucose metabolism participates in the development of IH ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…PKM2 can increase angiogenesis to support tumor growth and progression, according to a recent study [ 54 ]. Yang et al [ 55 ] mixed HemECs with overexpressed or knocked-down PKM2 with HUVECs and injected the mixture into the subcutaneous tissue of the left upper limb of 4-week-old male nude mice. Compared to the control group, knocking down PKM2 had the opposite effect on the color of the hemangioma transplants and the increase in VEGF compared to overexpression of PKM2.…”
Section: Model Of Cell Suspension Implantationmentioning
confidence: 99%
“…Recently, the metabolic activity of ECs, particularly glycolytic metabolism, has emerged as a key driver of angiogenesis (2). Yang et al discovered that PKM2, a critical glycolytic enzyme, promoted angiogenesis in HemECs, while suppression of PKM2 inhibited IH progression in a mouse model (3). Similarly, another study demonstrated that targeting FPFKB3 suppressed glycolysis and induced apoptosis in HemECs, effectively inhibiting angiogenesis (4).…”
mentioning
confidence: 99%